2006
DOI: 10.1080/13645700600958432
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar microdiscectomy and microendoscopic discectomy

Abstract: Lumbar microdiscectomy, which relies on the operating microscope for visualization, was first described in the late 1970s. This operation is considered the gold standard procedure for patients who require surgery for symptomatic lumbar disc herniation causing radiculopathy that has not improved with conservative measures. A new approach to the management of symptomatic lumbar disc herniation, microendoscopic discectomy, was introduced in 1997. This operation utilizes a tubular retractor system and a microendos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 13 publications
0
29
0
1
Order By: Relevance
“…Various studies have reported on outcomes of MD[2122] and TD[142324] and proved them to be better to open discectomy[213252627282930] but only few have compared outcomes of MD with TD. [3132]…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported on outcomes of MD[2122] and TD[142324] and proved them to be better to open discectomy[213252627282930] but only few have compared outcomes of MD with TD. [3132]…”
Section: Discussionmentioning
confidence: 99%
“…Williams [31] proposed in 1978 a conservative microsurgical approach to virgin herniated lumbar discs by making only a blunt perforation in the fibrous annular ring without an incision or curettage of the disc space. This conventional microdiscectomy technique is considered to be the gold standard procedure for patients who require surgery for symptomatic lumbar disc herniation refractory to conservative measures [6,22,32]. Two of the main complications after lumbar discectomy are the recurrence of radicular pain and disc herniation.…”
Section: Introductionmentioning
confidence: 99%
“…The herniated tissue with this technique is resected endoscopically using a small incision and a tubular retractor (16 or 18 mm in diameter). This microendoscopic discectomy (MED) has been known to cause less tissue damage than conventional open microdiscectomy procedures with a marked reduction in postoperative pain and muscle spasm, allowing the procedure to be performed in the outpatient setting, and enabling patients to return to their activities of daily living fast 6,15) . In addition, the MED group showed a lower incidence of persistent residual postoperative low back pain than the conventional microdiscectomy group one year after the operation 16) .…”
Section: Discussionmentioning
confidence: 99%
“…The microendoscopic discectomy (MED) was introduced by Foley and Smith 8) ; it was the first technique that addressed the shortcomings of the conventional subperiosteal approach. Many investigators have reported that MED is associated with less postoperative pain, a shorter hospital stay, and more rapid return to work 6,15) . However, the MED has some limitations related to a small operation field, visualized through a cylindrical tubular retractor 12) .…”
Section: Introductionmentioning
confidence: 99%